Absolute Freedom of Speech and Social Media: Deconstructing the Argument of Individual Self-Realization - Keberson Bresolin (Daimon)
The paper challenges the absolute conception of freedom of speech as an unconditional means for individual self-realization. Firstly, it discusses the positions of Scanlon and Redish, revealing the inherent vulnerabilities in their arguments. Subsequently, it argues against the view of unlimited freedom of speech as fundamental to self-realization. Finally, even if one were to accept the premise of self-realization as an axiom, social media would not qualify as suitable arenas for its actualization, given their inability to replicate the fundamental characteristics of a public sphere that favors open, plural, and rational debate. Keywords: self-realization, autonomy, Scanlon, social media, public sphere, Habermas.